DINAMIKA PERBEDAAN MADZHAB DALAM ISLAM (Studi terhadap Pengamalan Madzhab di Aceh) - Muhammad Zukhdi (Universitas Islam Negeri Ar-Raniry, 2017)
This study has a theme about the existency of school (mazhab) and different perspectives in Islam; a study of the practice of Islamic jurisprudence school in Aceh. Majority of Acehnese community is fanatic to school (mazhab), particularly mazhab Syafi’i, as the teacher teachIslamic jurisprudence school and use its book based on its genealogy. Different perspectives divide Acehnese community into two groups, namely traditional community and modern community. Traditional group adheres to the jurisprudence of four schools (Hanafi, Maliki, Syafi'i dan Hanbali), particularly, the school of Syafi'i. The existency of school (mazhab) and different perspectives in community continue to develop in Islam until now, including in Aceh. However, these differences are still difficult to accept by both traditional circles and modernist. To avoid the differences, it is suggested to deepen an understanding of Islamic jurisprudence; it is also suggested to the scholars and intellectuals to open an objective dialogue forum in both internal and eksternal level.